Acoustically targeted chemogenetics for the non-invasive control of neural circuits. (July 2018) - Szablowski, Jerzy; Lee-Gosselin, Audrey; Lue, Brian; Malounda, Dina; Shapiro, Mikhail
Abstract Neurological and psychiatric disorders are often characterized by dysfunctional neural circuits in specific regions of the brain. Existing treatment strategies, including the use of drugs and implantable brain stimulators, aim to modulate the activity of these circuits. However, they are not cell-type-specific, lack spatial targeting or require invasive procedures. Here, we report a cell-type-specific and non-invasive approach based on acoustically targeted chemogenetics that enables the modulation of neural circuits with spatiotemporal specificity. The approach uses ultrasound waves to transiently open the blood–brain barrier and transduce neurons at specific locations in the brain with virally encoded engineered G-protein-coupled receptors. The engineered neurons subsequently respond to systemically administered designer compounds to activate or inhibit their activity. In a mouse model of memory formation, the approach can modify and subsequently activate or inhibit excitatory neurons within the hippocampus, with selective control over individual brain regions. This technology overcomes some of the key limitations associated with conventional brain therapies. The combination of focused ultrasound and virally encoded receptors engineered to be activated by a designer drug enables, on intravenous administration of the drug, the non-invasive activation or inhibition of brain regions in mice, with cell-type and spatiotemporal specificity.